A new adaptive iterative learning control of finite-time hybrid function projective synchronization for unknown time-varying chaotic systems - Zhang, Chunli; Yan, Lei; Gao, Yangjie; Wang, Wenqing; Li, Keming; Wang, Duo; Zhang, Long (Frontiers in Physics, 2023)
A new adaptive iterative learning control (AILC) scheme is proposed to solve the finite time hybrid function projective synchronization (HFPS) problem of chaotic systems with unknown periodic time-varying parameters. Fourier series expansion (FSE) is introduced to deal with the problem of uncertain time-varying parameter. The bound of the expanded remainder is unknown. A typical convergent series is used to deal with the unknown bound in the design process of the controller. The adaptive iterative learning synchronization controller and parameter update laws are designed. Two different chaotic systems are synchronized asymptotically according to different proportional functions on a finite time interval by Lyapunov stability analysis. The simulation example proves the feasibility and effectiveness of the proposed method.